Keragaan Produktivitas Padi Sawah Jawa Barat Dan Faktor Yang Mempengaruhinya - Juri Juswadi; Pandu Sumarna; Neneng Sri Mulyati (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
This study aims to describe the performance of West Java wet land paddy productivity in the period 1997-2017, and identify the factors that influence it. Descriptive research results show that during the period 1997-2017, the average productivity of wet land paddy in West Java that observed from 16 districts experienced an increase from 53.22 Kw/ha in 1997 to 60.79 Kw/ha ton in 2017, with average productivity per year is 55.92 Kw/ha. Wet land paddy productivity has increased by 7.57 Kw/ha or an increase in an average of 0.83% per year. Increased productivity has fluctuated with a negative increase occurred in 1998, 2001, 2004, 2010, 2012, 2014, 2014, 2015 and 2017. There is still a gap between factual wet land paddy productivity with potential productivity of some superior varieties of wet land paddy. The results of statistical analysis of factors that affect wet land paddy productivity in West Java show that variable altitude and rainfall have a significant effect on wet land paddy productivity, while the irrigation area and cropping index (IP) have no significant effect